Developmental changes in the frequency and complexity of mothers' internal state utterances across the second year. Issue 4 (August 2019) - Olson, Janet; Masur, Elise Frank
Mothers' provision of utterances with internal state words has been shown to influence infants' acquisition of internal state vocabulary and has been proposed to foster preschoolers' theory of mind development. In this article the authors examine maternal internal state speech during free play with infants at 13, 17, and 21 months. The study assessed developmental changes in the frequency and complexity of the mothers' utterances referencing perception, volition, disposition, and cognition. Mothers' use of internal state words, especially volition and cognition words, increased with age. Internal state utterances were longer than utterances without internal state words, and more than half of all cognition and two-thirds of all volition utterances were syntactically complex. Mothers' production of utterances with internal state words was related to their overall MLUs whereas their production of utterances without was not. Thus, mothers do not simplify utterances when they talk about internal states, even with young infants, and mothers' growing use of internal state words as their infants age may partially explain increases in their overall utterance lengths during the second year of life.